Sustainability as a Value Creation Mechanism: A Conceptual Framework of ESG, Profitability, and Market Valuation - Yusron Toto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study empirically evaluates the role of sustainability in practices that influence firm value by explicitly modeling profitability as a transmission mechanism. Using a balanced panel of 51 firms listed on the Indonesia Stock Exchange over 2017–2023 (357 firm-year observations), the analysis applies a Random Effects model estimated using EGLS, selected through Chow, Hausman, and Lagrange Multiplier tests. The results indicate that ESG performance, carbon disclosure, and green innovation positively and significantly affect Return on Assets (ROA). Further estimations show that ESG performance, carbon disclosure, green innovation, and ROA exert positive and significant effects on firm value (Tobin’s Q), while firm size and leverage display negative and significant impacts. Mediation analysis using Sobel, Aroian, and Goodman tests confirms that ROA significantly mediates the relationship between each sustainability dimension and firm value. The models explain approximately 48% of the variation in ROA and 54% of the variation in firm value. Conceptually, the study integrates the Triple Bottom Line, Doughnut Economics, and modern capitalism into a unified framework linking sustainability practices to firm value through internal profitability.